2019
DOI: 10.1002/app.47777
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on thermal properties of microencapsulated phase‐change materials with different acrylate‐based copolymer shells as thermal insulation materials

Abstract: A series of microencapsulated phase‐change materials (micro‐PCMs) with binary cores and acrylate‐based copolymer shells were prepared. The micro‐PCMs contained octadecane and butyl stearate as binary‐core materials. Allyl methacrylate, ethylene glycol dimethacrylate, 1,4‐butanediol diacrylate (BDDA), and 1,6‐hexanediol dimethacrylate were respectively introduced to copolymerize with divinylbenzene (DVB) to form different microcapsule shells. In this work, the influence of the types of core and shell materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In addition, Wu et al also found that the thermal conductivity of PU was reduced to 0.25 W m −1 K −1 due to the restrained molecular movement, compared with that of pure PEG‐6000 (i.e., 0.31 W m −1 K −1 ) . Ma et al prepared a series of microencapsulated PCMs with binary cores and acrylate‐based copolymer shells and found that the wallboard fabricated with the synthesized microencapsulated PCMs showed an excellent thermal insulation performance . This can be attributed to the reduced thermal conductivity after encapsulation with copolymer shells, simply because the thermal insulation performance is positively correlated with a low thermal conductivity .…”
Section: Thermal Conduction Of Pcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Wu et al also found that the thermal conductivity of PU was reduced to 0.25 W m −1 K −1 due to the restrained molecular movement, compared with that of pure PEG‐6000 (i.e., 0.31 W m −1 K −1 ) . Ma et al prepared a series of microencapsulated PCMs with binary cores and acrylate‐based copolymer shells and found that the wallboard fabricated with the synthesized microencapsulated PCMs showed an excellent thermal insulation performance . This can be attributed to the reduced thermal conductivity after encapsulation with copolymer shells, simply because the thermal insulation performance is positively correlated with a low thermal conductivity .…”
Section: Thermal Conduction Of Pcmsmentioning
confidence: 99%
“…[37] Ma et al prepared a series of microencapsulated PCMs with binary cores and acrylate-based copolymer shells and found that the wallboard fabricated with the synthesized microencapsulated PCMs showed an excellent thermal insulation performance. [145] This can be attributed to the reduced thermal conductivity after encapsulation with copolymer shells, simply because the thermal insulation performance is positively correlated with a low thermal conductivity. [146] Meanwhile, Ma et al investigated the reduced thermal conductivity of the polymer.…”
Section: Thermal Conductivity Reduction Of Pcmsmentioning
confidence: 99%
“…As far as we know, hydrogels are three-dimensional network structures consisting of polymeric chains and are swollen in water up to thermodynamic equilibrium. , Inspired by the swelling effect of hydrogels, we wondered whether the polymers prepared by flexible linkers could expand their volume in the substrate solvent and thus facilitate the contact between the substrate and the active sites. To our delight, 1,4-butanediol diacrylate (BDDA) not only had a long flexible chain but also was an ideal connector of copolymers due to the direct connection between the ester carbonyl group and the alkene bond. Simultaneously, the high degree of cross-linking may cause the polymers to pack tightly, which was not conducive to the exposure of the active sites. Therefore, the A 4 -type porphyrins were adjusted to the A 2 B 2 -type porphyrins in order to reduce the degree of cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PCMs with low thermal conductivity can be used in building architecture, biological thermotherapy, and high technology (like infrared stealth). Ma et al. (2019 ) prepared the wallboard containing microencapsulated PCMs composed of binary cores and acrylate-based copolymer shells showing excellent thermal insulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PCMs with low thermal conductivity can be used in building architecture, biological thermotherapy, and high technology (like infrared stealth). Ma et al (2019) prepared the wallboard containing microencapsulated PCMs composed of binary cores and acrylate-based copolymer shells showing excellent thermal insulation performance. Chen et al (2020a) prepared 3D freestanding flexible CNT sponge-based PCMs with a low thermal conductivity for high-performance thermotherapy of allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%